Experimental evidence on the nature of the Danish employment miracle - Michael Rosholm (Institute for the Study of Labor (IZA), 2008)
This paper uses a social experiment in labour market policy - providing early and intensive monitoring and programme participation in unemployment spells - to assess the nature of labour market policy effectiveness. The experiment was conducted in two counties in Denmark during the winter of 2005-6. The treatment consisted of a dramatic intensification of labour market policies. The results show that the intensification of labour market policies is highly effective, leading to increases in the exit rate from unemployment ranging from 20 to 40%. When introducing time-varying indicators for the various specific treatments actually prescribed to the unemployed workers, none of those treatments have a positive effect on the exit rate from unemployment, neither during the week in which the activity takes place, nor after the activity is completed. However, when the estimated risk of participating in an activity is included as an explanatory variable, it removes the difference in job-finding rates between treatment and control groups completely in one of the counties, and reduces it dramatically and renders it insignificant in the other county. The interpretation we attach to these results is the following; since individual treatments do not appear to be effective per se, but the risk of treatment is, it must be that the intensification of the policy regime increases the job-finding rate of unemployed workers.
urn:nbn:de:101:1-2008081110
Keywords: J64; 330; Social experiment; labour market policy regime; treatment effect; threat effect; duration model; Arbeitsmarkt; Arbeitsmarktpolitik; Arbeitslosigkeit; Wirkungsanalyse; Test; Dänemark